Literature Study: Teaching Modules Based on Realistic Mathematics Approach to Improve Learning Outcomes of Elementary School Students Between 2019 - 2024 - Iftinawati, Sri; Handoyo, Eko; Wardani, Sri; Subali, Bambang; Widiarti, Nuni (research, training and philanthropy institution Natural Aceh, 2025)
This literature review departs from the problems in learning mathematics in elementary schools related to teaching abstract material, such as fractions, which affects the low achievement of student learning outcomes. This literature review aims to theoretically analyze the impact of using teaching modules based on the Realistic Mathematics Approach (PMR) in improving student learning outcomes in primary schools. The method used in this review is a Systematic Literature Review (SLR) covering 25 articles from five databases: Google Scholar, DOAJ, Sinta, ResearchGate, and Scopus. The articles were keyworded